Dissecting the molecular control of Interleukin 6 signaling using the M1 cell line. (October 2021) - Morris, Rhiannon; Hilton, Douglas J.; Jarratt, Andrew; Babon, Jeffrey J.
Abstract: Interleukin 6 is the classical member of the IL-6 family of cytokines which triggers activation of the JAK/STAT signaling cascade in cells. IL-6 is a pleiotropic cytokine that acts on many cell types and plays a critical role in immune responses, inflammation, and haematopoiesis. Our understanding of the molecular mechanisms governing IL-6 signaling has been aided by numerous studies of this signal transduction pathway, including those utilising the M1 cell line. Here we discuss the studies that we and others have undertaken using the M1 line to examine IL-6 inducible genes, particularly those targets that acts as negative regulators of signaling. Finally, we present a model for the current understanding of the IL-6 signaling pathway at a structural and mechanistic level.